A fuzzy logic model to determine the effects of die/blank holder angle and punch radius on drawing ratio in angular deep drawing dies - Ozek, Cebeli; Celik, Yahya Hisman; Ozek, Muzeyyen Bulut (Ios Press, 2013)
Deep drawing process is one of the widely used methods in sheet-metal forming. With the deep drawing method, products of various geometrical shapes such as saucepans, tubes, perfume and soft drink cans can be obtained easily. Therefore, the optimization of the deep drawing process is very important for the industry. In conventional deep drawing method, no angle is given to the surfaces of die and pressure plate. Both die and pressure plate and the geometrical shape of die and punch have a significant effect on drawing ratio. In this study, the effect of angles and radii on the drawing ratio of blank holder and punch forces were theoretically calculated and experimentally investigated in order to deep drawing the DIN EN 10130-91 sheet by giving angles on the die/blank holder surfaces and radii on the punch edge surfaces. In addition, the data obtained from the experimental study were calculated with the Fuzzy Logic Model and the optimum and the lowest drawing ratios for the die and punch radius as well as the die/blank holder were determined. The optimum drawing ratio in the experimental study was obtained as beta = 2.3, when the die and punch radius was R = 10 mm and the die/blank holder angle was theta = 12.5 degrees, and as beta = 2.2 in the Fuzzy Logic model. The lowest drawing ratio was obtained as beta = 1.8 when the blank holder angle was theta = 0 degrees in the experimental study and as beta = 1.82 in the Fuzzy Logic model.
Keywords: Deep drawing dies; The Fuzzy Logic; drawing ratio